Analisis Tingkat Kesehatan Bank Pembiayaan Rakyat Syariah (BPRS) Menggunakan Metode RGEC (Studi pada BPRS di Kota Semarang yang Terdaftar di OJK Periode 2019-2022) - Miranda, Ariadna Madyaratri; Wirman, Wirman (Peneliti.net, 2024)
Apart from providing loan funds for the community, health level of BPRS also needs to be considered so that they can carry out their roles and functions well. A poor level of health will have a negative impact on the performance and management of the bank and can endanger other parties such as customers who have entrusted their funds to be managed. To assess the level of health or good or bad performance of bank, it can be assessed using several indicator. Bank Indonesia uses the RBRR approach as a replacement for the previous method which was less effective. The research method used is descriptive quantitative. The data used is secondary data in the form of BPRS financial reports which can be accessed on the official website http://www.ojk.go.id. The result of the research show that based on the RGEC analysis that has been carried out at the BPRS in Semarang City, it categorized as healthy with PK value of 2, which means it classified as healthy so it is able to overcome all negative influences but there are still weaknesses that should be immediately acted upon or overcome.